Chloride corrosion behavior on heating pipeline made by AISI 304 and 316 in reclaimed water. Issue 61 (2nd December 2021) - Chen, Xi; Liu, Hongyan; Sun, Xiang; Zan, Botao; Liang, Meisheng
Abstract : It would be economical if heating pipes were used to transport reclaimed water during its idle period. The most important thing is to study the causes and processes of the corrosion on it for practical application. Abstract : In order to transport reclaimed water safely through stainless steel (SS) heat-supply pipeline networks during their idle period, one must understand the degree to which chlorine in reclaimed water is corrosive to SS. In this study, electrochemical methods were used to evaluate the corrosion resistances of two types of SS materials, AISI 304 and AISI 316, in simulated reclaimed water at chloride concentrations of 25 to 400 mg L −1, which are similar to those present in practice. The differences in corrosion resistance between the two types of SS material were investigated using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization tests (Tafel curves). The passivation layers on the two types of SS exhibited obvious similarities under several experimental conditions. However, EIS, polarization resistance, effective capacitance, Tafel curve, and Scanning Electron Microscope (SEM) data showed that AISI 316 has better corrosion resistance than AISI 304. The corrosion behaviours could be described as a series of reactions between Fe, Cr, and H2 O that generate several precipitated products such as Fe2 O3, Cr2 O3, FeOOH, and CrOOH.